My generation collected nonfiction - Styron, William 1925-2006 (Random House, 2015)
My Generation is the definitive gathering of William Styron’s nonfiction, exposing the core of this greatly gifted, highly convivial, and profoundly serious artist from his literary emergence in the 1950s to his death in 2006. Here are fifty years of Styron’s essays, memoirs, reviews, op-eds, articles, eulogies, and speeches, reflecting the same brilliant style and informed thinking that he brought to his towering fiction and to a deeply committed public life. Including many newly collected and never-before-published items, this compendium ranges from the original mission statement of The Paris Review, which Styron helped found in 1953, to a 2001 tribute to his friend Philip Roth—creating an essential overview of arts and letters during the post–World War II years.